Cancer prevention in females with and without obesity: does perceived and internalised weight bias determine cancer prevention behaviour? - Bernard, Marie; Löbner, Magrit; Lordick, Florian; Mehnert-Theuerkauf, Anja; Riedel-Heller, Steffi Gerlinde; Luck-Sikorski, Claudia (BMC women's health, 2022)
Cancer prevention, obesity, weight bias internalisation, stigma